Pre-lithiated positive electrode precursor and preparation method thereof, positive electrode material, positive electrode plate and battery

By introducing lithium elements into the spray pyrolysis positive electrode precursor for presintering, the problem of low tap density of the precursor is solved, and higher load density and battery energy density are achieved, reducing costs.

CN119612611AActive Publication Date: 2025-03-14ZHEJIANG HUAYOU COBALT CO LTD

Patent Information

Application Number
CN202411582083.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-03-14
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

The density of the positive electrode precursor prepared by spray pyrolysis is low, resulting in an increase in storage and transportation costs, and the density of the fashion bowl is low at high temperature sintering, which limits the increase in production capacity.

Method used

By mixing the spray pyrolysis precursor with the lithium source for presintering, lithium elements are introduced to promote grain growth and form a denser oxide structure, thereby improving tap density.

Benefits of technology

The tap density of spray pyrolysis high nickel positive electrode precursor is significantly improved, the loading density and bowl density is improved, storage and transportation costs are reduced, and the energy density and electrochemical performance of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005125993130000231
    Figure BDA0005125993130000231
  • Figure BDA0005125993130000232
    Figure BDA0005125993130000232
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, and discloses a pre-lithiated positive electrode precursor and a preparation method thereof, a positive electrode material, a positive electrode plate and a battery. The preparation method of the pre-lithiated positive electrode precursor comprises the following steps: preparing a mixed metal salt solution containing a nickel source, a manganese source and an M metal source; carrying out spray pyrolysis treatment on the mixed metal salt solution to obtain a spray pyrolysis precursor; and mixing the spray pyrolysis precursor with a first lithium source, and carrying out first sintering treatment to obtain the pre-lithiated positive electrode precursor. The lithium element is introduced into the core body of the precursor material through pre-lithiation, growth of precursor crystal grains is promoted, the lithium element has high reaction activity, oxidation and rearrangement of metal ions can be promoted, formation of a more compact oxide structure is facilitated, the size of the crystal grains is increased, hollowing is reduced, and the performance of the material is improved. Therefore, the tap density of the spray pyrolysis positive electrode precursor is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a pre-lithiation positive electrode precursor and a preparation method thereof, a positive electrode material, a positive electrode plate and a battery. Background Art

[0002] Layered oxide cathode precursors are key components in the preparation of lithium-ion battery cathode materials. This material is usually composed of transition metals (such as nickel, cobalt, manganese, etc.) and oxygen elements. In the subsequent high-temperature solid-phase reaction, it will react with lithium salts to form layered oxide cathode materials.

[0003] At present, the mainstream mass production preparation methods of layered oxide cathode precursors mainly include co-precipitation and spray pyrolysis. The co-precipitation method is to mix a variety of metal salt solutions with a precipitant solution, and control the reaction conditions to precipitate the metal ions together to form a precursor with a layered structure. The spray pyrolysis method atomizes the metal salt solution and then performs a pyrolysis reaction in a high temperature environment to prepare an ultra-fine powdered layered oxide cathode precursor.

[0004] Compared with the coprecipitation method, the spray pyrolysis method has the advantages of short process path, fewer key process parameters, low production cost, and high sintering reaction activity. Compared with the coprecipitation precursors of the same composition, the spray pyrolysis method can sinter single crystal positive electrode materials at a lower temperature, especially for precursors that are more sensitive to sintering temperature, such as positive electrode precursors with high nickel content, the spray pyrolysis method has more application value.

[0005] However, the positive electrode precursor prepared by spray pyrolysis has small particle size and hollowness, which will reduce the tap density of the precursor, increase the storage and transportation cost per ton of precursor, and cause low packing density during high-temperature sintering, limiting the increase in production capacity. Summary of the invention

[0006] In view of the above problems, the present application provides a pre-lithiation positive electrode precursor and a preparation method thereof, a positive electrode material, a positive electrode plate and a battery, aiming to solve the problem of low tap density of the spray pyrolysis positive electrode precursor.

[0007] In a first aspect, an embodiment of the present application provides a method for preparing a pre-lithiation positive electrode precursor, comprising the following steps: preparing a mixed metal salt solution of a nickel source, a manganese source and an M metal source; wherein the M metal source contains at least one of cobalt salts, aluminum salts, zirconium salts, tantalum salts, titanium salts, niobium salts, germanium salts, yttrium salts, tungsten salts, boron salts, cerium salts and strontium salts; subjecting the mixed metal salt solution to a spray pyrolysis treatment to obtain a spray pyrolysis precursor; mixing the spray pyrolysis precursor with a first lithium source and subjecting the mixture to a first sintering treatment to obtain the pre-lithiation positive electrode precursor.

[0008] The preparation method of the embodiment of the present application is to pre-sinter the spray pyrolysis precursor with an appropriate amount of lithium source, and introduce the lithium element into the core of the precursor material through the pre-lithiation process, which promotes the growth of the precursor grains. Since the lithium element has high reactivity, it can promote the oxidation and rearrangement of metal ions, and help to form a more compact oxide structure. This process increases the grain size to a certain extent and reduces the hollowing phenomenon, thereby significantly improving the tap density of the spray pyrolysis high nickel positive electrode precursor. This improvement not only improves the loading density and the bowl density, but also reduces the storage and transportation costs, and has the effect of reducing costs and increasing output. In addition, this process also causes the impurity elements to migrate to the surface of the particles, so that these impurities can be quickly removed by simple water washing.

[0009] In some embodiments, the spray pyrolysis treatment step includes: spray pyrolyzing the mixed metal salt solution at a temperature of 500°C to 1000°C for 20s to 120s, wherein the atomization flow rate of the mixed metal salt solution is 20L / min to 200L / min, the carrier gas flow rate is 50L / min to 500L / min, and the ratio of the carrier gas flow rate to the atomization flow rate is 2 to 3.

[0010] By adopting the above technical solution, it is helpful to better control the particle size of the spray pyrolysis precursor product to be kept within the ideal target range. The D50 of the prepared spray pyrolysis precursor is

[0011] 0.5μm~3.5μm, Dmax is less than 30μm, specific surface area is 4m 2 / g~16m 2 / g.

[0012] In some embodiments, the ratio of the molar amount of lithium element in the first lithium source to the total molar amount of metal elements in the spray pyrolysis precursor is 0.5 to 1; and / or, the temperature of the first sintering treatment is 350°C to 650°C, and the time is 0.5h to 4h.

[0013] By controlling the above process conditions, the growth and aggregation of the precursor particles can be promoted, so that the particle size of the precursor increases to an ideal range, thereby improving the tap density of the pre-lithiation precursor.

[0014] In a second aspect, the present invention provides a pre-lithiation cathode precursor, wherein the chemical formula of the pre-lithiation cathode precursor is Li a Ni x Mn y M 1-x-y O z, 0.46≤a≤0.98, 0.5≤x≤0.95, y>0, 1≤z≤2; wherein M includes at least one of Co, Al, Zr, Ta, Ti, Nb, Ge, Y, W, B, Ce, and Sr.

[0015] In the embodiment of the present application, lithium is introduced into the core of the precursor material without affecting the activity of the precursor. The subscript a represents each Li a Ni x Mn y M 1-x-y O z The number of Li atoms in the molecule is a. When the value of a is within the above range, it helps to promote the uniform growth of the positive electrode precursor particles, helps to improve the density and stability of the material, and the dense crystal structure helps to reduce the hollowing phenomenon, thereby significantly improving the tap density of the spray pyrolysis high-nickel positive electrode precursor.

[0016] In some embodiments, the pre-lithiation cathode precursor is prepared by the preparation method of the pre-lithiation cathode precursor of the first aspect.

[0017] In some embodiments, the pre-lithiation cathode precursor has at least one of the following (1) to (3):

[0018] (1) The D50 of the pre-lithiation cathode precursor is 0.8 μm to 5 μm;

[0019] (2) The content of S element in the pre-lithiation positive electrode precursor is less than 200 ppm;

[0020] (3) The content of Cl element in the pre-lithiation positive electrode precursor is less than 100 ppm.

[0021] Due to the introduction of lithium, the D50 particle size of the pre-lithiation cathode precursor is larger than that of the spray pyrolysis precursor, and its tap density reaches 1.5g / cm 3 ~2.2g / cm 3 The low content of impurities such as S and Cl in the material helps to form a more uniform and dense crystal structure in the subsequent sintering process, thereby improving the electrochemical performance of the positive electrode material.

[0022] In a third aspect, the present application provides a positive electrode material, which is prepared by the pre-lithiation positive electrode precursor prepared by the preparation method described in the first aspect or the pre-lithiation positive electrode precursor described in the first aspect, and the chemical formula of the positive electrode material is Li a1 Ni x1 Mn y1 M 1-x1-y1O2, 1.02≤a1≤1.10, 0.5≤x1≤0.95, 0.01≤y1≤0.4, wherein M includes at least one of Co, Al, Zr, Ta, Ti, Nb, Ge, Y, W, B, Ce, and Sr.

[0023] The positive electrode material is prepared by using the pre-lithiation positive electrode precursor of the first aspect or the second aspect. Since the pre-lithiation positive electrode precursor has a high tap density, its particles are closely arranged and the internal structure is more compact, the formed positive electrode material has a better energy density. Moreover, the impurity content of the pre-lithiation positive electrode precursor is low, and the positive electrode material prepared by using this precursor has better structural stability and electrochemical performance.

[0024] In some embodiments, the cathode material has at least one of the following (I) to (III):

[0025] (I) The D50 of the positive electrode material is 2.8 μm to 4.3 μm, and the Dmax is less than 15 μm;

[0026] (II) The specific surface area of ​​the positive electrode material is 0.35 m 2 / g~0.85m 2 / g;

[0027] (III) The mass fraction of residual lithium in the positive electrode material is 0.02 wt% to 0.06 wt%.

[0028] In a fourth aspect, an embodiment of the present application provides a method for preparing a positive electrode material, comprising the following steps: mixing a pre-lithiation positive electrode precursor with a second lithium source and performing a second sintering treatment to obtain the positive electrode material.

[0029] Since the pre-lithiation cathode precursor has a higher tap density, it has better fluidity and plasticity during processing, making the cathode material preparation process smoother and improving production efficiency. At the same time, it also helps to prepare cathode material particles with regular morphology and uniform particle size distribution.

[0030] In some embodiments, the molar ratio of the lithium element in the second lithium source to the metal element in the spray pyrolysis precursor is 0.06 to 0.66; and / or, the temperature of the second sintering treatment is 700° C. to 950° C.; and the time is 6 h to 14 h.

[0031] In a fifth aspect, an embodiment of the present application provides a positive electrode sheet, the positive electrode sheet comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector, the positive electrode active material layer comprising the positive electrode material described in the third aspect, or the positive electrode material obtained by the preparation method of the positive electrode material described in the fourth aspect. In this way, the quality of the electrode sheet is improved.

[0032] In a sixth aspect, an embodiment of the present application provides a battery, comprising the positive electrode sheet as described in the fifth aspect. In this way, the energy density of the battery is improved, and the charging and discharging efficiency of the battery is improved.

[0033] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. DETAILED DESCRIPTION

[0034] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0035] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0036] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all mean: a, b, c, ab (i.e. a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0037] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0038] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0039] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.

[0040] The cathode precursors prepared by spray pyrolysis usually have a small particle size. In addition, during the spray pyrolysis process, due to the rapid evaporation and decomposition of the droplets, hollow structures may form inside some oxide particles. The combination of small particle size and hollowing results in a low tap density of the prepared cathode precursor, which is not conducive to the subsequent material processing and battery performance improvement.

[0041] Based on this, an embodiment of the present application provides a method for preparing a pre-lithiation positive electrode precursor, comprising the following steps: preparing a mixed metal salt solution containing a nickel source, a manganese source and an M metal source; wherein the M metal source contains at least one of cobalt salts, aluminum salts, zirconium salts, tantalum salts, titanium salts, niobium salts, germanium salts, yttrium salts, tungsten salts, boron salts, cerium salts and strontium salts; subjecting the mixed metal salt solution to a spray pyrolysis treatment to obtain a spray pyrolysis precursor; mixing the spray pyrolysis precursor with a first lithium source and subjecting the mixture to a first sintering treatment, and then washing and drying the mixture to obtain a pre-lithiation positive electrode precursor.

[0042] Pre-lithiation is a technology that introduces lithium elements in advance during the preparation of positive electrode materials. The pre-lithiation technology of the embodiment of the present application aims to promote the increase of the particle size of the positive electrode precursor by pre-introducing the lithium element into the core of the precursor material, thereby increasing the tap density of the precursor. Tap density refers to the mass of a powder per unit volume measured after vibration compaction under specified conditions. For lithium battery positive electrode materials, a higher tap density means more mass of active material per unit volume, which is beneficial to improving the energy density and volume capacity of the battery.

[0043] Wherein, the nickel source, manganese source, and M metal source refer to compounds used to provide nickel element, manganese element, and M metal element, respectively. For example, the nickel source can be selected from nickel salts, such as at least one of nickel nitrate, nickel chloride, nickel sulfate, nickel carbonate, nickel bicarbonate, nickel oxalate, and nickel acetate. The manganese source can be selected from manganese salts, such as at least one of manganese nitrate, manganese chloride, manganese sulfate, manganese carbonate, manganese bicarbonate, manganese oxalate, and manganese acetate. The M metal source can be selected from at least one of nitrates, chlorides, sulfates, manganese carbonates, manganese bicarbonates, manganese oxalate, and manganese acetate containing M metal elements.

[0044] The step of preparing a mixed metal salt solution containing a nickel source, a manganese source and an M metal source may include: dissolving a metal salt of a nickel salt, a manganese salt and an M metal in an aqueous solution according to a predetermined metal element ratio, thereby preparing a mixed metal salt solution. This mixed metal salt solution may be an unsaturated solution, that is, under specific metal salt and its ratio conditions, none of the metal salts reaches its saturation concentration. The main metal elements contained in the mixed metal salt solution include nickel (Ni) and manganese (Mn). In addition, at least one element of cobalt (Co), aluminum (Al), zirconium (Zr), tantalum (Ta), titanium (Ti), niobium (Nb), germanium (Ge), yttrium (Y), tungsten (W), boron (B), cerium (Ce) and strontium (Sr) may be added according to actual needs. In some embodiments, the molar proportion of the nickel (Ni) element in all metal elements exceeds 50%.

[0045] The principle of spray pyrolysis treatment is to spray a solution containing metal salts into a high temperature environment in the form of mist. Under this condition, the solvent evaporates rapidly and the metal salts are then thermally decomposed. Then, due to the occurrence of supersaturation, the metal salts are converted into solid form and crystallized, thereby directly forming nano-scale powders. The spray pyrolysis treatment of the embodiment of the present application can be carried out by passing a mixed metal salt solution into a spray pyrolysis furnace.

[0046] The spray pyrolysis precursor has a small and uniform particle size and exhibits excellent reactivity after combining with a lithium source. This property enables them to achieve grain boundary fusion and grain growth at a relatively low temperature and in a short time, thereby significantly improving the tap density of the pre-lithiation cathode precursor. At the same time, as the lithium element is embedded in the lattice structure of the cathode material and the grains grow further, those impurity elements such as sulfur and chlorine that originally existed in the precursor and could not be integrated into the lattice of the cathode material will be squeezed to the surface of the grains, making it easier to remove by washing with water. Thanks to the increase in grain size and the reduction in specific surface area, the obtained pre-lithiation cathode precursor not only has improved fluidity, but the water in it is also easier to evaporate and dry, which greatly improves the processing performance of the cathode precursor.

[0047] In some embodiments, the step of spray pyrolysis treatment includes: spray pyrolysis of the metal salt solution at a temperature of 500°C to 1000°C for 20s to 120s, wherein the atomization flow rate of the metal salt solution after entering the spray pyrolysis furnace is 20L / min to 200L / min, the spray carrier gas is selected from at least one of air or oxygen, the carrier gas flow rate is 50L / min to 500L / min, and the ratio of the carrier gas flow rate to the atomization flow rate is 2 to 3.

[0048] As an example, the spray pyrolysis temperature can be 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C, etc., which are typical but non-limiting values, and the spray pyrolysis time can be 20s, 40s, 60s, 80s, 100s, 120s, etc., which are typical but non-limiting values. The pyrolysis temperature affects the evaporation rate of the solvent in the droplets and the rate and degree of the thermal decomposition reaction. The pyrolysis time affects the reaction time of the droplets at high temperature, and affects the phase composition and grain growth of the product. Controlling the spray pyrolysis temperature and pyrolysis time within the above range can better promote the crystallization and sintering of the product.

[0049] As an example, the atomization flow rate can be a typical but non-limiting value such as 20L / min, 50L / min, 150L / min, 200L / min, etc. Correspondingly, since the ratio between the carrier gas flow rate and the atomization flow rate is constrained to 2 to 3, the carrier gas flow rate can be set to a typical but non-limiting value such as 40L / min to 60L / min, 100L / min to 150L / min, 300L / min to 450L / min, 400L / min to 600L / min. The atomization flow rate affects the generation and size distribution of droplets, and thus affects the particle size and morphology of the product. The carrier gas flow rate affects the reaction rate and the crystallinity of the product. By adjusting the atomization flow rate and the carrier gas flow rate to the above range, it helps to better control the particle size of the product to remain within the predetermined target range.

[0050] By controlling the process conditions of the spray pyrolysis treatment within the above range, the D50 particle size of the obtained spray pyrolysis precursor is 0.5μm to 3.5μm, the Dmax is not more than 30μm, and the specific surface area is 4m 2 / g

[0051] ~16m 2 / g. D50 is often used to indicate the average particle size of powders. Dmax particle size refers to the maximum particle size in the particle size distribution. It is used together with other particle size distribution percentiles such as D10, D50 and D90 to reflect the maximum particle size in the particle sample and, to a certain extent, the width of the particle size distribution range.

[0052] In some embodiments, the spray pyrolysis product (spray pyrolysis precursor) is separated from the tail gas by a cyclone separation device and a gas classifier, and the tail gas can be reused in the carrier gas circulation system after being treated by the tail gas treatment device. The cyclone separation device here refers to a device for separating the spray pyrolysis product from the gas. The gas classifier can classify the materials collected by the cyclone separation and separate the fine particles that meet the particle size requirements.

[0053] In the step of mixing the spray pyrolysis precursor with the first lithium source and then performing the first sintering treatment, the first lithium source can be selected from at least one of lithium hydroxide monohydrate, lithium hydroxide, lithium oxide, lithium peroxide, lithium carbonate, and lithium nitrate. As an example, the first lithium source can be a single type of lithium source, such as pure lithium hydroxide or pure lithium carbonate, or a mixture of multiple lithium sources, such as a mixture of lithium hydroxide and lithium carbonate. When multiple lithium sources are selected, the mixing ratio is not limited.

[0054] In some embodiments, the ratio of the molar amount of lithium elements in the first lithium source to the total molar amount of metal elements in the spray pyrolysis precursor is defined as the first lithium ratio, and the first lithium ratio is 0.5 to 1. The total molar amount of metal elements in the spray pyrolysis precursor here refers to the total number of moles of all metal elements (such as nickel, manganese, M metal elements, etc.) in the spray pyrolysis precursor. If the first lithium ratio is too low, it will be unfavorable for the growth of the pre-lithiation positive electrode precursor; if the first lithium ratio is too high, it will lead to waste of lithium. Therefore, the first lithium ratio is controlled at 0.5 to 1, so that the grain boundary fusion and grain growth can be completed in a short time at a lower temperature, thereby improving the tap density of the precursor material. As an example, the first lithium ratio can be typical but non-limiting values ​​such as 0.5, 0.6, 0.7, 0.8, 0.9, 1, etc. Since the subsequent water washing and impurity removal process will cause some lithium loss, the chemical formula of the pre-lithiation precursor finally prepared is Li a Ni x Mn y M 1-x-y O z The subscript a of Li in is in the range of 0.46 to 0.98.

[0055] In some embodiments, the temperature of the first sintering treatment is 350°C to 650°C, and the time is 0.5h to 4h. As an example: the temperature of the first sintering treatment can be 350°C, 450°C, 500°C, 550°C, 600°C, 650°C and other typical but non-limiting values, and the time of the first sintering treatment can be 0.5h, 1.0h, 1.5h, 2.0h, 2.5h, 3.0h, 3.5h, 4.0h and other typical but non-limiting values. The first sintering treatment does not limit the sintering atmosphere, for example, it can be carried out in an air environment. The equipment for the first sintering treatment can be an industrial kiln such as a rotary kiln or a roller kiln.

[0056] Through the above-mentioned first sintering treatment, the spray pyrolysis precursor and the appropriate amount of lithium source can promote the growth or aggregation of particles in the high-temperature sintering step, thereby increasing the particle size of the final pre-lithiation positive electrode precursor. Since too long a sintering time or too high a sintering temperature may cause the precursor particles to be too large, thereby adversely affecting the quality of the precursor, the embodiment of the present application can finely control the temperature and time of the first sintering to increase the precursor particle size to an ideal range, thereby improving the tap density of the pre-lithiation precursor.

[0057] After the first sintering treatment, the product of the first sintering is transferred to a water washing and stirring tank, water is added and stirred, and then washed, filtered to remove impurities, and dried to obtain a pre-lithiation positive electrode precursor. During the water washing process, in order to reduce lithium loss, the mass ratio of the amount of water used for water washing to the product of the first sintering is controlled in the range of 1.25:1 to 3:1. As an example: the mass ratio can be 1.25:1, 1.5:1, 2:1, 2.5:1, 3:1 and other typical but non-limiting values. The water washing stirring speed should not be too fast, the stirring speed can be 100rpm to 900rpm, and the water washing stirring time can be 3min to 10min.

[0058] Due to the limitations of preparation conditions, the raw materials used in the preparation of positive electrode precursors by spray pyrolysis are mostly transition metal chlorides and transition metal sulfates with high solubility and mild decomposition. These transition metal salts contain more impurity elements such as chlorine and sulfur. These impurity elements will be brought into the spray pyrolysis products and finally remain in the positive electrode precursor and positive electrode materials, thus adversely affecting product performance. Therefore, in order to remove impurity elements, the industry usually washes the spray pyrolysis positive electrode precursor with water. However, since the spray pyrolysis oxide precursor has a small particle size and is prone to agglomeration, simple water washing cannot quickly clean the impurities, and the washed material will not be easy to dehydrate and dry, resulting in problems such as high moisture content, poor fluidity, and easy agglomeration of the spray precursor.

[0059] In the embodiment of the present application, a spray pyrolysis precursor obtained by spray pyrolysis is first mixed with an appropriate amount of lithium source and pre-sintered, and then impurities are removed by water washing and filtration, and finally dried to obtain a pre-lithiation positive electrode precursor with extremely low impurity content and high tap density.

[0060] In some embodiments, in order to reduce the content of impurity elements in the material, the moisture content of the material after washing and filtration needs to be controlled within 20000ppm. The drying process can be carried out under negative pressure conditions, and dry gas is continuously introduced to remove water vapor on the surface of the material. The drying temperature can be set between 110°C and 130°C.

[0061] The pre-lithiation cathode precursor prepared by the above preparation method has a D50 of 0.8 μm to 5 μm and a tap density of 1.5 g / cm 3 ~2.2g / cm 3 , with a specific surface area of ​​3m 2 / g~10m 2 / g. Due to the increase in grain size and the decrease in specific surface area, the prepared pre-lithiation cathode precursor has good fluidity, which makes it easier to dry the moisture in the material, thereby improving the processing performance of the precursor.

[0062] The content of magnetic foreign matter such as Fe, Cr, Zn, Cu in the pre-lithiation positive electrode precursor prepared by the above preparation method is within 15ppm, that is, the content of any of the above magnetic foreign matter in the pre-lithiation positive electrode precursor does not exceed 15ppm. The magnetic foreign matter here refers to substances that can be attracted or magnetized under the action of a magnetic field. These substances may be objects that are originally magnetic, or objects that are magnetic after being magnetized under the action of an external magnetic field. In the lithium battery industry, these foreign matter may include transition elements such as metal single substances such as iron (Fe), chromium (Cr), copper (Cu), zinc (Zn) and their alloys, which may undergo electrochemical reactions inside the battery to form dendrites, pierce the battery separator and electrolyte, and cause a series of problems such as battery short circuit and self-discharge.

[0063] The mass fraction of residual lithium in the pre-lithiation positive electrode precursor prepared by the above preparation method is within 0.02wt%. The residual lithium here usually refers to lithium compounds such as Li2CO3, LiHCO3 and LiOH that remain on the surface of the material due to various reasons during the preparation of the positive electrode material of the lithium-ion battery. The presence of these residual lithium compounds will not only lead to the instability of the material structure, but also cause the reduction of electrochemical performance and may even cause battery safety problems. The residual lithium can usually be removed by washing with water, and the mass fraction of the residual lithium can be determined by point titration.

[0064] In a second aspect, the present invention provides a pre-lithiation cathode precursor, the chemical formula of which is Li a Ni x Mn y M 1-x-y O z , 0.46≤a≤0.98, 0.5≤x≤0.95, y>0, 1≤z≤2; wherein M includes at least one of Co, Al, Zr, Ta, Ti, Nb, Ge, Y, W, B, Ce, and Sr.

[0065] The chemical formula of the pre-lithiation cathode precursor is Li a Ni x Mn y M 1-x-y Oz In which, the subscript a represents each Li a Ni x Mn y M 1-x-y O z The number of Li atoms in the molecule is a, and the value range of a is 0.46 to 0.98. As an example, the value of a can be 0.46, 0.50, 0.55, 0.60, 0.65, 0.70, 0.75, 0.80, 0.85, 0.90, 0.95, 0.98 and other typical but non-limiting values. The content of lithium has an important influence on the crystal structure of the material. When the content of lithium is within the above range, it helps to promote the uniform growth of the positive electrode precursor particles, helps to improve the density and stability of the material, and the dense crystal structure helps to reduce the hollowing phenomenon. The subscript x represents each Li a Ni x Mn y M 1-x-y O z The number of Ni atoms in the molecule is x, and the value of x ranges from 0.5 to 0.95. For example, the value of x can be 0.50, 0.55, 0.60, 0.65, 0.70, 0.75, 0.80, 0.85, 0.90, 0.95, etc., which are typical but non-limiting values. The subscript y represents each Li a Ni x Mn y M 1-x-y O z The number of Ni atoms in the molecule is y, and the value range of y is y>0. As an example, the value of y can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.25, 0.30, 0.35, 0.40, 0.45, 0.50, 0.55, 0.60, 0.65, 0.70, 0.75, 0.80, 0.85, 0.90, 0.95 and other typical but non-limiting values. The subscript z represents each Li a Ni x Mn y M 1-x-y O zThe number of O atoms in the molecule is z, and the value range of y is 1≤z≤2. As an example, the value of z can be 1.00, 1.01, 1.02, 1.03, 1.04, 1.05, 1.06, 1.07, 1.08, 1.09, 1.10, 1.11, 1.12, 1.13, 1.14, 1.15, 1.16, 1.17, 1.18, 1.19, 1.20, 1.21, 1.22, 1.23, 1.24, 1.25, 1.30, 1.35, 1.40, 1.45, 1.50, 1.55, 1.60, 1.65, 1.70, 1.75, 1.80, 1.85, 1.90, 1.95, 2.00, etc., which are typical but non-limiting values. The positive electrode precursor in the embodiment of the present application contains a higher proportion of Ni element, which gives the material a higher specific capacity, thereby improving the energy density of the battery. If the lithium element is not introduced, the high-nickel positive electrode precursor may tend to have a smaller particle size to shorten the diffusion path of lithium ions and improve the rate performance of the material. The pre-lithiated positive electrode precursor in the embodiment of the present application introduces lithium elements into the core of the precursor material, promotes grain growth and reduces hollowing through pre-lithiation, thereby improving the tap density of the spray pyrolysis high-nickel positive electrode precursor.

[0066] In some embodiments, the pre-lithiation positive electrode precursor is prepared by the preparation method of the first aspect.

[0067] In some embodiments, the D50 of the pre-lithiation cathode precursor is 0.8 μm to 5 μm. D50 represents the midpoint value of the particle size distribution in the particle population, that is, particles with a particle size less than D50 account for 50% of the total particle mass or number, and particles with a particle size greater than D50 also account for 50% of the total particle mass or number. The D50 particle size is often used to describe the average particle size characteristics of powder or granular materials. It is one of the important indicators for evaluating particle size distribution. As an example, the D50 of the pre-lithiation cathode precursor can be 0.8 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm and other typical but non-limiting values. Due to the introduction of lithium, the D50 particle size of the pre-lithiation cathode precursor is larger than that of the spray pyrolysis precursor, thereby increasing the tap density, and its tap density reaches 1.5 g / cm 3 ~2.2g / cm 3 , which is equivalent to the tap density of the precursor mixed with lithium prepared by co-precipitation method.

[0068] In some embodiments, the content of S element in the pre-lithiation positive electrode precursor is less than 200ppm. If the content of impurity elements such as sulfur and chlorine in the positive electrode precursor is too high, it may destroy the layered structure of the positive electrode material, reduce its structural stability, and also cause the capacity decay and cycle stability of the positive electrode material to decrease. Therefore, in the preparation process of the positive electrode precursor, it is necessary to strictly control the impurity content of the precursor. The sulfur content of the pre-lithiation positive electrode precursor of the embodiment of the present application is less than 200ppm, which helps to improve the sintering performance, enhance the density and uniformity of the material, and help maintain the uniformity and consistency of the particles.

[0069] In some embodiments, the Cl content in the pre-lithiation cathode precursor is less than 100 ppm. As an impurity, the chlorine content is less than 100 ppm, which is conducive to forming a more uniform and dense crystal structure during the subsequent heat treatment process, thereby improving the electrochemical performance of the cathode material.

[0070] In a third aspect, the present application provides a positive electrode material, which is prepared by using the pre-lithiation positive electrode precursor of the first aspect or the second aspect, and the chemical formula of the positive electrode material is Li a1 Ni x1 Mn y1 M 1-x1-y1 O2, 1.02≤a1≤1.10, 0.5≤x1≤0.95, 0.01≤y1≤0.4, wherein M includes at least one of Co, Al, Zr, Ta, Ti, Nb, Ge, Y, W, B, Ce, and Sr.

[0071] The positive electrode material of the embodiment of the present application is made of a pre-lithiated positive electrode precursor, and the tap density of the pre-lithiated positive electrode precursor is high, which means that the particles are relatively dense, which is conducive to maintaining the stability of the structure during the high-temperature sintering process, thereby improving the energy density of the positive electrode material. Moreover, the impurity content of the pre-lithiated positive electrode precursor is low, which means that the purity of the precursor material is high, so the active material content of the prepared positive electrode material is relatively high, which improves the electrochemical performance and structural stability of the positive electrode material.

[0072] In some embodiments, the D50 of the positive electrode material is 2.8 μm to 4.3 μm, and the Dmax is less than 15 μm; the specific surface area of ​​the positive electrode material is 0.35 to 0.85 m 2 / g; the mass fraction of residual lithium in the positive electrode material is 0.02wt% to 0.06wt%.

[0073] In a fourth aspect, an embodiment of the present application provides a method for preparing a positive electrode material, comprising the following steps: mixing a pre-lithiation positive electrode precursor with a second lithium source and performing a second sintering treatment to obtain a positive electrode material.

[0074] The second lithium source can be selected from at least one of lithium hydroxide monohydrate, lithium hydroxide, lithium oxide, lithium peroxide, lithium carbonate, and lithium nitrate. The composition of the second lithium source is not affected by the first lithium source, and the same lithium source or different lithium sources can be selected.

[0075] In some embodiments, the ratio of the molar amount of lithium in the second lithium source to the total molar amount of metal elements in the spray pyrolysis precursor is defined as the second lithium ratio, and the second lithium ratio is 0.06 to 0.66. As an example, the second lithium ratio can be 0.06, 0.1, 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.66 and other typical but non-limiting values. The value of the second lithium ratio is related to the first lithium ratio. In order to make the lithium content in the positive electrode material reach the desired value, the sum of the first lithium ratio and the second lithium ratio is 1.06 to 1.16. Since the washing step in the preparation process of the pre-lithiation positive electrode precursor will lose a part of the lithium element, the final positive electrode material Li a1 Ni x1 Mn y1 M 1-x1-y1 The subscript a1 of the Li element in O2 is 1.02 to 1.10.

[0076] In some embodiments, the temperature of the second sintering treatment is 700℃~950℃; the sintering time is 6h~14h. As an example, the sintering temperature can be 700℃, 750℃, 800℃, 850℃, 900℃, 950℃ and other typical but non-limiting values, and the sintering time can be 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h and other typical but non-limiting values. The specific sintering temperature and sintering time are related to the nickel content in the positive electrode material. Generally, when the nickel element accounts for 50% to 80% of the total molar number of non-lithium metal elements, the second sintering temperature is set at 920℃~960℃, the sintering time is 10h~14h, and the material performance is better; when the nickel element accounts for more than 80% of the total molar number of non-lithium metal elements, the second sintering temperature is set at 740℃~800℃, the sintering time is 6h~12h, and the material performance is better. The sintering atmosphere includes at least one of air and oxygen, and the volume fraction of oxygen therein is greater than 21%.

[0077] In some embodiments, after the second sintering treatment, mechanical crushing is required after cooling, including but not limited to jaw crushing, roller crushing, ball mill crushing, etc., and at least one screening can be performed between the mechanical crushing and air flow mill crushing steps. The mesh number of the sieve is more than 200 meshes, and the grinding pressure of the air flow mill crushing is 0.2~1.0MPa.

[0078] The positive electrode material prepared by the above preparation method has a low residual lithium mass fraction, a moderate D50 particle size and a specific surface area, and has good electrochemical performance.

[0079] In a fifth aspect, an embodiment of the present application provides a positive electrode sheet, the positive electrode sheet comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector, the positive electrode active material layer comprising the positive electrode material described in the third aspect, or the positive electrode material obtained by the preparation method of the positive electrode material described in the fourth aspect. In this way, the quality of the electrode sheet is improved.

[0080] In a sixth aspect, an embodiment of the present application provides a battery, comprising the positive electrode sheet as described in the fifth aspect. In this way, the energy density of the battery is improved, and the charging and discharging efficiency of the battery is improved.

[0081] The following describes the invention in conjunction with specific embodiments.

[0082] Example 1

[0083] (1) Preparation of pre-lithiation cathode precursor

[0084] The present invention provides a pre-lithiation cathode precursor, the chemical formula of which is Li 0.68 Ni 0.6 Mn 0.1 Co 0.3 O2. The preparation method of the pre-lithiation positive electrode precursor comprises the following steps:

[0085] S1: 34.75 kg (120 mol) of nickel nitrate hexahydrate, 5.00 kg (20 mol) of manganese nitrate tetrahydrate, and 17.39 kg (60 mol) of cobalt nitrate hexahydrate were weighed in a molar ratio of 6:1:3, and dissolved in 24 L of water to obtain a metal salt solution.

[0086] S2: The metal salt solution is atomized in a spray pyrolysis furnace at an atomization flow rate of 20 L / min. The spray carrier gas is a mixture of air and oxygen at a volume fraction of 1:1. The carrier gas flow rate is 60 L / min. The temperature of the spray pyrolysis furnace is set to 770 ° C. The pyrolysis time of the material in the pyrolysis furnace is 60 s. The product obtained by the spray pyrolysis is separated from the tail gas by a cyclone separation device, and the spray pyrolysis precursor Ni is collected. 0.6 Mn 0.1 Co 0.3 O 1.14 .

[0087] S3: According to the first lithium ratio of 0.72, 4.2kg (56.8mol) of lithium carbonate and 12kg (75.89 158mol) of spray pyrolysis precursor were weighed (the "first lithium ratio" was defined as the ratio of the molar amount of lithium element in lithium carbonate to the total molar amount of metal elements in the spray pyrolysis precursor). After the materials were mixed evenly, they were first sintered at 550°C for 3h. The sintering atmosphere was dry air with an air flow rate of 20L / min. The materials after the first sintering were crushed, screened, washed and filtered. After the water content of the solid material was less than 20000ppm, it was transferred to a slightly negative pressure environment and dried at 120°C for 1h to obtain a pre-lithiated positive electrode precursor. During the washing process, the mass ratio of water consumption to the first sintering product was 2:1, the washing speed was 400rpm, the washing time was set to 6min, and the negative pressure was maintained at -0.8 to -1.0MPa during the filtration process after washing.

[0088] (2) Preparation of positive electrode materials

[0089] The chemical formula of the positive electrode material is Li 1.06 Ni 0.6 Mn 0.1 Co 0.3 O2. The preparation method of the positive electrode material comprises the following steps:

[0090] It has been determined that the actual first lithium ratio in the pre-lithiation cathode precursor is 0.68, so 3.0 kg of lithium carbonate is weighed and mixed evenly with the above-mentioned pre-lithiation cathode precursor (13.5 kg) according to the second lithium ratio of 0.38 (the "second lithium ratio" is defined as the ratio of the molar amount of lithium element in lithium carbonate to the total molar amount of metal elements in the spray pyrolysis precursor). After mixing, a small amount of sample is taken for tap density (TD) test, and the rest is poured into a sagger and placed in a high-temperature sintering furnace for the second sintering treatment. The second sintering condition is set as follows: at a heating rate of 5 ° C / min, first rise to 750 ° C for sintering for 1h, then rise to 920 ° C for sintering for 12h, and the sintering atmosphere is a mixture of air and oxygen at a volume fraction of 1:2. After sintering, the material is crushed by rollers and sieved through a 200-mesh screen before being crushed by airflow milling. The grinding pressure of airflow milling is 0.40 MPa.

[0091] After testing, the impurity content and particle size distribution of the precursor before and after pre-lithiation are shown in Table 1; the tap density (TD) value of the mixture of the pre-lithiation positive electrode precursor and lithium carbonate is 1.89 g / cm 3 , which is equivalent to the TD value of the coprecipitated precursor after lithium mixing; the D50 of the prepared single crystal positive electrode material is 3.8μm, Dmax is 12μm, and the specific surface area (BET) is 0.68m 2 / g, the residual lithium mass fraction of the positive electrode material is 0.04wt%, and the impurity content and 0.2C first charge and discharge performance of the positive electrode material are shown in Table 2.

[0092] Example 2

[0093] The difference between Example 2 and Example 1 is that metal chloride salt is selected as the raw material for preparing the spray pyrolysis precursor.

[0094] (1) Preparation of pre-lithiation cathode precursor

[0095] The pre-lithiation cathode precursor provided in Example 2 has a chemical formula of Li 0.66 Ni 0.6 Mn 0.1 Co 0.3 O2. The preparation method of the pre-lithiation positive electrode precursor comprises the following steps:

[0096] S1: Weigh 36.03 kg, 5.00 kg and 18.03 kg of nickel chloride hexahydrate, manganese chloride tetrahydrate and cobalt chloride hexahydrate respectively in a molar ratio of 6:1:3, and dissolve them in 112 L of water to obtain a metal salt solution.

[0097] S2: The metal salt solution is introduced into the spray pyrolysis furnace for atomization at an atomization flow rate of 25 L / min. The spray carrier gas is a mixture of air and oxygen at a volume fraction of 1:1. The carrier gas flow rate is 70 L / min. The temperature of the spray pyrolysis furnace is set to 800 °C. The pyrolysis time of the material in the pyrolysis furnace is 80 s. The product obtained by the spray pyrolysis is separated from the tail gas by a cyclone separation device, and the spray pyrolysis precursor Ni is collected. 0.6 Mn 0.1 Co 0.3 O 1.14 .

[0098] S3: According to the first lithium ratio of 0.72, 5.6kg of lithium carbonate and 16kg of spray pyrolysis precursor are weighed (wherein, the definition of "first lithium ratio" is the ratio of the molar amount of lithium element in lithium carbonate to the total molar amount of metal elements in the spray pyrolysis precursor), and the mixture is evenly mixed and then sintered for 3h at 560°C. The sintering atmosphere is dry air with an air flow rate of 20L / min. The material after the first sintering is crushed, screened, washed and filtered. After the water content of the solid material is lower than 20000ppm, it is transferred to a slightly negative pressure environment and dried at 120°C for 1h to obtain a pre-lithiated positive electrode precursor. During the washing process, the mass ratio of water consumption to the first sintering product is 1.5:1, the washing speed is 500rpm, the washing time is set to 7min, and the negative pressure is maintained at -0.8~-1.0MPa during the filtration process after washing.

[0099] (2) Preparation of positive electrode materials

[0100] The chemical formula of the positive electrode material is Li 1.06 Ni 0.6 Mn 0.1 Co0.3 O2. The preparation method of the positive electrode material comprises the following steps:

[0101] It was determined that the actual first lithium ratio in the pre-lithiation cathode precursor was 0.66. Therefore, 4.2 kg of lithium carbonate was weighed and mixed evenly with the above-mentioned pre-lithiation cathode precursor (18.0 kg) according to the second lithium ratio of 0.40. After mixing, a small amount of sample was taken for tap density (TD) test, and the rest was poured into a sagger and placed in a high-temperature sintering furnace for the second sintering treatment. The second sintering condition was set as follows: at a heating rate of 5 ° C / min, first rise to 750 ° C for sintering for 1.5h, then rise to 925 ° C for sintering for 12h, and the sintering atmosphere was a mixture of air and oxygen at a volume fraction of 1:2. After sintering, the material was crushed by rollers, sieved through a 200-mesh screen, and then crushed by air jet mill. The grinding pressure of the air jet mill is 0.45MPa.

[0102] After testing, the impurity content and particle size distribution of the precursor before and after pre-lithiation are shown in Table 1; the tap density (TD) value of the mixture of the pre-lithiation positive electrode precursor and lithium carbonate is 1.92 g / cm 3 , which is equivalent to the TD value of the coprecipitated precursor after lithium mixing; the D50 of the prepared single crystal positive electrode material is 3.7μm, Dmax is 11μm, and the specific surface area (BET) is 0.71m 2 / g, the residual lithium mass fraction of the positive electrode material is 0.04wt%, and the impurity content and 0.2C first charge and discharge performance of the positive electrode material are shown in Table 2.

[0103] Example 3

[0104] The difference between Example 3 and Example 2 is that the first lithium ratio is 0.77, and the pre-lithiation positive electrode precursor provided in Example 3 has a chemical formula of Li 0.73 Ni 0.6 Mn 0.1 Co 0.3 O2.

[0105] (1) Preparation of pre-lithiation cathode precursor

[0106] The method for preparing the pre-lithiation positive electrode precursor comprises the following steps:

[0107] S1: Weigh 36.03 kg, 5.00 kg and 18.03 kg of nickel chloride hexahydrate, manganese chloride tetrahydrate and cobalt chloride hexahydrate respectively in a molar ratio of 6:1:3, and dissolve them in 112 L of water to obtain a metal salt solution.

[0108] S2: The metal salt solution is introduced into the spray pyrolysis furnace for atomization at an atomization flow rate of 25 L / min. The spray carrier gas is a mixture of air and oxygen at a volume fraction of 1:1. The carrier gas flow rate is 70 L / min. The temperature of the spray pyrolysis furnace is set to 800 °C. The pyrolysis time of the material in the pyrolysis furnace is 80 s. The product obtained by the spray pyrolysis is separated from the tail gas by a cyclone separation device, and the spray pyrolysis precursor Ni is collected. 0.6 Mn 0.1 Co 0.3 O 1.14 .

[0109] S3: According to the first lithium ratio of 0.77, 6.0kg of lithium carbonate and 16kg of spray pyrolysis precursor were weighed, and after the materials were evenly mixed, the first sintering was carried out at 560°C for 3h. The sintering atmosphere was dry air, and the air flow rate was 20L / min. The materials after the first sintering were crushed, screened, washed and filtered. After the water content of the solid material was lower than 20000ppm, it was transferred to a slightly negative pressure environment and dried at 120°C for 1h to obtain a pre-lithiation positive electrode precursor. During the washing process, the mass ratio of water consumption to the first sintering product was 1.5:1, the washing speed was 500rpm, the washing time was set to 7min, and the negative pressure was maintained at -0.8 to -1.0MPa during the filtration process after washing.

[0110] (2) Preparation of positive electrode materials

[0111] The chemical formula of the positive electrode material is Li 1.06 Ni 0.6 Mn 0.1 Co 0.3 O2. The preparation method of the positive electrode material comprises the following steps:

[0112] It was determined that the actual first lithium ratio in the pre-lithiation cathode precursor was 0.73. Therefore, 3.64 kg of lithium carbonate was weighed according to the second lithium ratio of 0.33 and mixed evenly with the above-mentioned pre-lithiation cathode precursor (18.8 kg). After mixing, a small amount of sample was taken for TD test, and the rest was poured into a sagger and placed in a high-temperature sintering furnace for sintering. The sintering conditions were set as follows: at a heating rate of 5 ° C / min, first rise to 750 ° C for sintering for 1.5 hours, and then rise to 925 ° C for sintering for 12 hours. The sintering atmosphere was a mixture of air and oxygen at a volume fraction of 1:2. After sintering, the material was crushed by rollers, sieved through a 200-mesh screen, and then crushed by air jet mill. The grinding pressure of the air jet mill was 0.45 MPa.

[0113] After testing, the impurity content and particle size distribution of the precursor before and after pre-lithiation are shown in Table 1; the TD value of the mixture of pre-lithiation positive electrode precursor and lithium carbonate is 1.94g / cm 3, which is equivalent to the TD value of the coprecipitated precursor after lithium mixing; the D50 of the prepared single crystal positive electrode material is 3.6μm, Dmax is 11μm, and BET is 0.70m 2 / g, the residual lithium mass fraction of the single crystal positive electrode material is 0.04wt%, and the impurity content of the single crystal positive electrode material and the 0.2C first charge and discharge performance are shown in Table 2.

[0114] Example 4

[0115] The difference between Example 4 and Example 2 is that the ratio of nickel, cobalt and manganese elements is changed. The pre-lithiation positive electrode precursor provided in Example 4 has a chemical formula of Li 0.68 Ni 0.8 Mn 0.1 Co 0.1 O2.

[0116] (1) Preparation of pre-lithiation cathode precursor

[0117] The method for preparing the pre-lithiation positive electrode precursor comprises the following steps:

[0118] S1: Weigh 48.04 kg, 5.00 kg and 6.01 kg of nickel chloride hexahydrate, manganese chloride tetrahydrate and cobalt chloride hexahydrate, respectively, at a molar ratio of 8:1:1, and dissolve them in 53 L of water to obtain a metal salt solution.

[0119] S2: The metal salt solution is introduced into the spray pyrolysis furnace at a flow rate of 25 L / min for atomization. The spray carrier gas is a mixture of air and oxygen at a volume fraction of 1:1. The carrier gas flow rate is 70 L / min. The temperature of the spray pyrolysis furnace is set to 790 ° C. The pyrolysis time of the material in the pyrolysis furnace is 80 s. The product obtained by the spray pyrolysis is separated from the tail gas by a cyclone separation device, and the spray pyrolysis precursor Ni is collected. 0.8 Mn 0.1 Co 0.1 O 1.06 .

[0120] S3: According to the first lithium ratio of 0.72, 3.63kg and 16kg of lithium hydroxide and spray pyrolysis precursor were weighed, and the mixture was evenly sintered at 520°C for 2h. The sintering atmosphere was dry air with an air flow rate of 20L / min. The sintered materials were crushed, screened, washed and filtered. After the water content of the solid material was lower than 20000ppm, it was transferred to a slightly negative pressure environment and dried at 120°C for 1h to obtain a pre-lithiated positive electrode precursor, wherein the water washing solid-liquid ratio was 1.5:1, the water washing speed was 500rpm, the water washing time was set to 7min, and the negative pressure was maintained at -0.8~-1.0MPa during the filtration process after water washing.

[0121] (2) Preparation of positive electrode materials

[0122] The chemical formula of the positive electrode material is Li 1.06 Ni 0.8 Mn 0.1 Co 0.1 O2. The preparation method of the positive electrode material comprises the following steps:

[0123] It was determined that the actual first lithium ratio in the pre-lithiation cathode precursor was 0.68, so 2.62 kg of lithium hydroxide was weighed according to the second lithium ratio of 0.38 and mixed evenly with the above-mentioned pre-lithiation cathode precursor (18.0 kg). After mixing, a small amount of sample was taken for TD test, and the rest was poured into a sagger and placed in a high-temperature sintering furnace for sintering. The sintering conditions were set as follows: at a heating rate of 5 ° C / min, first rise to 600 ° C for 1h, then rise to 780 ° C for 12h, and the sintering atmosphere was pure oxygen. After sintering, the material was crushed by rollers, sieved through a 200-mesh screen, and then crushed by air jet mill. The grinding pressure of the air jet mill was 0.78 MPa.

[0124] After testing, the impurity content and particle size distribution of the precursor before and after pre-lithiation are shown in Table 1; the TD value of the mixture of pre-lithiation positive electrode precursor and lithium carbonate is 1.97g / cm 3 , which is equivalent to the TD value of the coprecipitated precursor after lithium mixing; the D50 of the prepared single crystal positive electrode material is 3.6μm, Dmax is 13μm, and the specific surface area BET is 0.65m 2 / g, the residual lithium mass fraction of the single crystal positive electrode material is 0.06wt%, and the impurity content of the single crystal positive electrode material and the 0.2C first charge and discharge performance are shown in Table 2.

[0125] Comparative Example 1

[0126] The difference between Comparative Example 1 and Example 2 is that the precursor is not pre-lithiated, and the spray pyrolysis precursor is directly washed and impurities are removed after preparation. At this time, a longer washing time is required to more effectively remove impurities. At the same time, due to the small particle size of the spray pyrolysis precursor, the filtration time will also be correspondingly extended.

[0127] (1) Preparation of spray pyrolysis precursor

[0128] The specific steps are as follows:

[0129] S1: 36.03 kg, 5.00 kg and 18.03 kg of nickel chloride hexahydrate, manganese chloride tetrahydrate and cobalt chloride hexahydrate were weighed in a molar ratio of 6:1:3, respectively, and dissolved in 112 L of water to obtain a first reaction solution.

[0130] S2: The first reaction liquid is introduced into a spray pyrolysis furnace for atomization at a flow rate of 25 L / min. The spray carrier gas is a mixture of air and oxygen in a volume fraction of 1:1. The carrier gas flow rate is 70 L / min. The temperature of the spray pyrolysis furnace is set to 800°C. The pyrolysis time of the material in the pyrolysis furnace is 80s. The product obtained by the spray pyrolysis is separated from the exhaust gas by a cyclone separation device, and the spray pyrolysis precursor is collected.

[0131] S3: Pour the spray pyrolysis precursor into pure water at a mass ratio of 1.5:1 between the spray pyrolysis precursor and water. The washing speed is 500 rpm and the washing time is 14 h, which is 120 times the washing and impurity removal time of the pre-lithiation positive electrode precursor. The negative pressure is maintained at -0.8 to -1.0 MPa during the filtration process after washing. After the water content in the solid material is less than 20000 ppm, it is transferred to a slightly negative pressure environment and dried at 120 ° C for 1 h to obtain a dry spray pyrolysis precursor Ni 0.6 Mn 0.1 Co 0.3 O 1.14 .

[0132] (2) Preparation of positive electrode materials

[0133] Preparation of single crystal positive electrode material: 9.29 kg of lithium carbonate was weighed according to the first lithium ratio of 1.06 and mixed evenly with the above-mentioned spray pyrolysis precursor. After mixing, a small amount of sample was taken for TD test, and the rest was poured into a sagger and placed in a high-temperature sintering furnace for sintering. The sintering conditions were set as follows: at a heating rate of 5 ° C / min, first raised to 750 ° C for 4 hours, and then raised to 925 ° C for 12 hours. The sintering atmosphere was a mixture of air and oxygen at a volume fraction of 1:2. After sintering, the material was crushed by rollers, sieved through a 200-mesh screen, and then crushed by a jet mill. The grinding pressure of the jet mill was 0.45 MPa.

[0134] After testing, the impurity content and particle size distribution of the precursor are shown in Table 1; the TD value of the mixture of precursor and lithium carbonate is 1.38g / cm 3 , which is much smaller than the pre-lithiation cathode precursor; the D50 of the prepared single crystal cathode material is 3.1μm, Dmax is 32μm, and BET is 0.78m 2 / g, the residual lithium mass fraction of the single crystal positive electrode material is 0.07wt%, and the impurity content of the single crystal positive electrode material and the 0.2C first charge and discharge performance are shown in Table 2.

[0135] Comparative Example 2

[0136] The difference between Comparative Example 2 and Example 1 is that the first lithium ratio is 0.25, and the pre-lithiation precursor obtained therefrom still has a lot of impurities after washing with water, and the primary particles are still relatively small, resulting in a prolonged subsequent filtration time.

[0137] (1) Preparation of pre-lithiation cathode precursor

[0138] The method for preparing the pre-lithiation positive electrode precursor comprises the following steps:

[0139] S1: Weigh 36.03 kg, 5.00 kg and 18.03 kg of nickel chloride hexahydrate, manganese chloride tetrahydrate and cobalt chloride hexahydrate respectively in a molar ratio of 6:1:3, and dissolve them in 112 L of water to obtain a metal salt solution.

[0140] S2: The metal salt solution is introduced into the spray pyrolysis furnace for atomization at an atomization flow rate of 25 L / min. The spray carrier gas is a mixture of air and oxygen at a volume fraction of 1:1. The carrier gas flow rate is 70 L / min. The temperature of the spray pyrolysis furnace is set to 800 °C. The pyrolysis time of the material in the pyrolysis furnace is 80 s. The product obtained by the spray pyrolysis is separated from the tail gas by a cyclone separation device, and the spray pyrolysis precursor Ni is collected. 0.6 Mn 0.1 Co 0.3 O 1.14 .

[0141] S3: Weigh 1.95kg and 16kg of lithium carbonate and spray pyrolysis precursor respectively according to the lithium metal ratio of 0.25, mix them evenly and sinter them at 560℃ for 3h. The sintering atmosphere is dry air with an air flow rate of 20L / min. The sintered materials are crushed, screened, washed and filtered. After the water content of the solid material is lower than 20000ppm, it is transferred to a slightly negative pressure environment and dried at 120℃ for 1h to obtain a pre-lithiation positive electrode precursor, wherein the water washing solid-liquid ratio is 1.5:1, the water washing speed is 500rpm, the water washing time is set to 28min, and the negative pressure is maintained at -0.8~-1.0MPa during the filtration process after water washing.

[0142] (2) Preparation of positive electrode materials

[0143] It was determined that the actual first lithium ratio in the pre-lithiation cathode precursor was 0.23. Therefore, 7.52 kg of lithium carbonate was weighed according to the second lithium ratio of 0.83 and mixed evenly with the above pre-lithiation cathode precursor. After mixing, a small amount of sample was taken for TD test, and the rest was poured into a sagger and placed in a high-temperature sintering furnace for sintering. The sintering conditions were set as follows: at a heating rate of 5 ° C / min, first rise to 750 ° C for sintering for 2.5 hours, then rise to 925 ° C for sintering for 12 hours, and the sintering atmosphere was a mixture of air and oxygen at a volume fraction of 1:2. After sintering, the material was crushed by rollers, sieved through a 200-mesh screen, and then crushed by air jet mill. The grinding pressure of the air jet mill was 0.45 MPa.

[0144] After testing, the impurity content and particle size distribution of the precursor before and after pre-lithiation are shown in Table 1; the TD value of the mixture of pre-lithiation positive electrode precursor and lithium carbonate is 1.45g / cm 3, which is much smaller than the pre-lithiation cathode precursor of Example 2; the D50 of the prepared single crystal cathode material is 3.6 μm, Dmax is 12 μm, and BET is 0.73 m 2 / g, the residual lithium mass fraction of the single crystal positive electrode material is 0.04wt%, and the impurity content of the single crystal positive electrode material and the 0.2C first charge and discharge performance are shown in Table 2.

[0145] Comparative Example 3

[0146] The difference between Comparative Example 3 and Example 2 is that all the lithium salts for preparing the single crystal positive electrode material are added at one time during the pre-lithiation of the precursor, and lithium is not added step by step. At this time, due to the low pre-lithiation temperature of the precursor and the short reaction time, the lithium element cannot be completely converted into lattice lithium in the single crystal positive electrode material. During the subsequent water washing treatment, the lithium remaining on the surface of the material is easily dissolved in the water, causing lithium loss, resulting in lithium deficiency in the final positive electrode material lattice, forming structural defects, and even transforming into a spinel or rock salt structure, losing electrochemical activity.

[0147] (1) Preparation of positive electrode materials

[0148] The chemical formula of the positive electrode material is Li 1.06 Ni 0.6 Mn 0.1 Co 0.3 O2. The preparation method of the positive electrode material comprises the following steps:

[0149] S1: Weigh 36.03 kg, 5.00 kg and 18.03 kg of nickel chloride hexahydrate, manganese chloride tetrahydrate and cobalt chloride hexahydrate respectively in a molar ratio of 6:1:3, and dissolve them in 112 L of water to obtain a metal salt solution.

[0150] S2: The metal salt solution is atomized in a spray pyrolysis furnace at an atomization flow rate of 25 L / min. The spray carrier gas is a mixture of air and oxygen in a volume fraction of 1:1. The carrier gas flow rate is 70 L / min. The temperature of the spray pyrolysis furnace is set to 800°C. The pyrolysis time of the material in the pyrolysis furnace is 80 s. The product obtained by the spray pyrolysis is separated from the exhaust gas by a cyclone separation device and collected to obtain a spray pyrolysis precursor.

[0151] S3: According to the first lithium ratio of 1.06, 8.26kg and 16kg of lithium carbonate and spray pyrolysis precursor were weighed, and the mixture was evenly sintered at 650°C for 3h. The sintering atmosphere was dry air with an air flow rate of 20L / min. The sintered materials were crushed, screened, washed and filtered. After the water content of the solid material was lower than 20000ppm, it was transferred to a slightly negative pressure environment and dried at 120°C for 1h to obtain a pre-lithiated positive electrode precursor, wherein the water washing solid-liquid ratio was 1.5:1, the water washing speed was 500rpm, the water washing time was set to 7min, and the negative pressure was maintained at -0.8~-1.0MPa during the filtration process after water washing.

[0152] S4: The actual first lithium ratio in the pre-lithiation cathode precursor was determined to be 0.92. A small amount of dried pre-lithiation cathode precursor samples were taken for TD testing, and the rest were placed in a sagger and sintered in a high-temperature sintering furnace. The sintering conditions were set as follows: at a heating rate of 5°C / min, first sintered at 750°C for 1h, then sintered at 925°C for 12h, and the sintering atmosphere was a mixture of air and oxygen at a volume fraction of 1:2. After sintering, the material was crushed by rollers, sieved through a 200-mesh screen, and then crushed by a jet mill. The grinding pressure of the jet mill was 0.45MPa.

[0153] After testing, the impurity content and particle size distribution of the precursor before and after pre-lithiation are shown in Table 1; the TD value of the pre-lithiation positive electrode precursor is 2.10g / cm 3 , which is higher than the TD value of the co-precipitated precursor after lithium mixing; the D50 of the prepared single crystal positive electrode material is 5.6μm, Dmax is 26μm, and BET is 0.54m 2 / g, the residual lithium mass fraction of the single crystal positive electrode material is 0.06wt%, the impurity content of the single crystal positive electrode material and the 0.2C first charge and discharge performance are shown in Table 2, and the first charge and discharge performance is significantly reduced.

[0154] Performance Testing

[0155] In order to verify the progress of the embodiments of the present application, the samples of the embodiments and comparative examples were tested as follows:

[0156] 1. Material particle size distribution test

[0157] The Malvern 3000 wet particle size analyzer was used for measurement, and the reference standard process was GB / T19077-2016 / ISO13320:2009. The specific test process was as follows: take an appropriate amount of the sample to be tested (the sample concentration is guaranteed to be 8-12% shading), add 20 ml NMP, and simultaneously ultraviolet for 5 minutes (53 KHz / 120 W) to ensure that the sample is completely dispersed, and then measure the sample according to the GB / T19077-2016 / ISO13320:2009 standard.

[0158] 2. Tap density test

[0159] Refer to GB / T 5162-2021 "Determination of tap density of metal powders" and use a tap density meter for measurement.

[0160] 3. Element analysis test

[0161] The inductively coupled plasma spectrometer (ICP, instrument model: PE Optima 7000DV) was used to test the content of Li, other metal elements and impurities in the positive electrode material. First, an appropriate amount of powder sample was weighed, and about 10 mL of aqua regia was added. The sample was heated for 30 to 50 minutes in a flat plate heating environment at about 185°C to fully digest the sample, and then tested on the machine.

[0162] Battery performance test

[0163] The positive electrode materials of Examples 1 to 4 and Comparative Examples 1 to 3 are used to prepare button batteries: the positive electrode materials, conductive agent carbon black, and binder polyvinylidene fluoride (PVDF) are mixed in a weight ratio of 7:2:1 and evenly coated on aluminum foil to make electrode sheets, which are then vacuum dried; the surface density of the electrode sheets is designed to be 4 to 5 mg.cm -2 In an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), the organic solvents ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed evenly in a volume ratio of 3 / 7, 12.5% ​​LiPF6 lithium salt was added and dissolved in the organic solvent, stirred evenly, and used as the electrolyte to assemble into button cells for testing.

[0164] The impurity content and particle size distribution data of the spray pyrolysis precursors prepared by the preparation methods of Examples 1 to 4 and Comparative Examples 1 to 3 before and after pre-lithiation are shown in Table 1 below, where the impurity content is tested using the ICP national standard test method, and the particle size distribution is measured using a Malvern 3000 wet particle size analyzer. The results show that the precursor products after spray drying in the Examples and Comparative Examples have high contents of non-metallic impurity elements such as S and Cl, high contents of magnetic foreign metal elements such as Fe, Cr, Cu, and Zn, and little difference in particle size distribution. However, after pre-lithiation and water washing treatment, in Examples 1 to 4, the contents of impurities such as S and Cl can be greatly reduced, and the contents of magnetic foreign metal elements such as Fe, Cr, Cu, and Zn can also be controlled at a relatively low level. The particle size distribution test shows that the particle size of the pre-lithiation positive electrode precursor particles has grown to a certain extent. In Comparative Examples 1 and 2 without pre-lithiation or too little pre-lithiation, due to insufficient lithium insertion and insufficient growth of precursor particle size, the internal impurity elements cannot be fully discharged to the grain surface, and still have high impurity contents such as S and Cl and metal elements such as Fe, Cr, Cu, and Zn. For Comparative Example 3 with excessive pre-lithiation, the impurity content and particle size distribution of the pre-lithiation precursor are at the same level as those of the embodiment, but excessive addition of lithium elements will cause waste of raw materials and increase costs.

[0165] Table 1

[0166]

[0167] The first charge and discharge is carried out in constant current constant voltage charge-constant voltage discharge mode, the charge and discharge voltage range is 2.8~4.4V, the charge rate is 0.2C, the charge cut-off current is 0.05C, the discharge rate is 0.2C, and the nominal capacity 1C is 200mAhg -1 The impurity content and 0.2C first charge and discharge performance of the positive electrode materials prepared by the preparation methods of Examples 1 to 4 and Comparative Examples 1 to 3 are shown in Table 2 below.

[0168] Table 2

[0169]

[0170] From the data in Table 2, it can be seen that the positive electrode material after the precursor is fully lithiated by high-temperature sintering inherits the impurity content in the precursor, and the samples without pre-lithiation treatment or too little pre-lithiation still contain a high impurity content. The results of the first charge and discharge test show that the first charge and discharge performance of the samples washed with pre-lithiation is better than that of the samples without pre-lithiation treatment or too much or too little pre-lithiation.

[0171] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.

Claims

1. A method for preparing a pre-lithiation cathode precursor, characterized in that: The following steps are involved: A mixed metal salt solution containing a nickel source, a manganese source and an M metal source is prepared; wherein the M metal source contains at least one of cobalt salt, aluminum salt, zirconium salt, tantalum salt, titanium salt, niobium salt, germanium salt, yttrium salt, tungsten salt, boron salt, cerium salt and strontium salt; The mixed metal salt solution is subjected to a spray pyrolysis treatment to obtain a spray pyrolysis precursor; The spray pyrolysis precursor is mixed with a first lithium source and then subjected to a first sintering treatment to obtain the pre-lithiation positive electrode precursor.

2. The method for preparing a pre-lithiation cathode precursor according to claim 1, characterized in that: The spray pyrolysis treatment step includes: spray pyrolyzing the mixed metal salt solution at a temperature of 500°C to 1000°C for 20s to 120s, wherein the atomization flow rate of the mixed metal salt solution is 20L / min to 200L / min, the carrier gas flow rate is 50L / min to 500L / min, and the ratio of the carrier gas flow rate to the atomization flow rate is 2 to 3.

3. The method for preparing a pre-lithiation cathode precursor according to claim 1 or 2, characterized in that: The ratio of the molar amount of lithium element in the first lithium source to the total molar amount of metal elements in the spray pyrolysis precursor is 0.5 to 1; and / or, The temperature of the first sintering treatment is 350° C. to 650° C., and the time is 0.5 h to 4 h.

4. A pre-lithiation cathode precursor, characterized in that: The general chemical formula of the pre-lithiation cathode precursor is Li a Ni x Mn y M 1-x-y O z , 0.46≤a≤0.98, 0.5≤x≤0.95, y>0, 1≤z≤2; wherein M includes at least one of Co, Al, Zr, Ta, Ti, Nb, Ge, Y, W, B, Ce, and Sr.

5. The pre-lithiation cathode precursor according to claim 4, characterized in that: The pre-lithiation positive electrode precursor is prepared by the method for preparing a pre-lithiation positive electrode precursor according to any one of claims 1 to 3.

6. The pre-lithiation cathode precursor according to claim 5, characterized in that: The pre-lithiation cathode precursor has at least one of the following (1) to (3): (1) The D50 of the pre-lithiation cathode precursor is 0.8 μm to 5 μm; (2) The content of S element in the pre-lithiation positive electrode precursor is less than 200 ppm; (3) The content of Cl element in the pre-lithiation positive electrode precursor is less than 100 ppm.

7. A positive electrode material, characterized in that: A pre-lithiated positive electrode precursor prepared by the preparation method according to any one of claims 1 to 3, or a pre-lithiated positive electrode precursor prepared by any one of claims 4 to 6, wherein the chemical formula of the positive electrode material is Li a1 Ni x1 Mn y1 M 1-x1-y1 O2, 1.02≤a1≤1.10, 0.5≤x1≤0.95, 0.01≤y1≤0.4, wherein M includes at least one of Co, Al, Zr, Ta, Ti, Nb, Ge, Y, W, B, Ce, and Sr.

8. The positive electrode material according to claim 7, characterized in that The positive electrode material has at least one of the following (I) to (III): (I) The D50 of the positive electrode material is 2.8 μm to 4.3 μm; (II) The specific surface area of ​​the positive electrode material is 0.35 to 0.85 m 2 / g; (III) The mass fraction of residual lithium in the positive electrode material is 0.02 wt% to 0.06 wt%.

9. A method for preparing a positive electrode material according to claim 7 or 8, characterized in that: The method comprises the following steps: mixing a pre-lithiation positive electrode precursor with a second lithium source and performing a second sintering treatment to obtain the positive electrode material.

10. The method for preparing the positive electrode material according to claim 9, characterized in that: The ratio of the molar amount of the lithium element in the second lithium source to the total molar amount of the metal elements in the spray pyrolysis precursor is 0.06 to 0.66; and / or, The temperature of the second sintering treatment is 700° C. to 950° C., and the time is 6 hours to 14 hours.

11. A positive electrode sheet, characterized in that: The positive electrode plate includes a positive electrode current collector and a positive electrode active material layer arranged on at least one side of the positive electrode current collector, and the positive electrode active material layer includes the positive electrode material as described in claim 7 or 8, or the positive electrode material obtained by the preparation method of the positive electrode material as described in claim 9 or 10.

12. A battery, characterized in that: Comprising the positive electrode sheet as claimed in claim 11.

Citation Information

Patent Citations

  • Layered large-particle-size high-nickel single-crystal ternary positive electrode material and preparation method thereof

    CN113644262A

  • Low-cobalt ternary single crystal material, preparation method thereof and lithium ion battery positive electrode material

    CN114275830A

Cited By

  • Composite metal oxide precursor, preparation method thereof, positive electrode material and battery

    CN120736578A

  • Positive eletrode, and lithium secondary battery including the same

    KR102998176B1